2003
DOI: 10.1002/hup.540
|View full text |Cite
|
Sign up to set email alerts
|

Prolonged QTc intervals in medicated patients with schizophrenia

Abstract: Psychotropic drugs have been associated with sudden deaths and the lengthening of corrected-QT interval (QTc) on the electrocardiogram which may be a precursor of life-threatening arrhythmias as reported with some of these drugs. The objectives of this study were to measure the frequency of QTc lengthening in patients with schizophrenia receiving psychotropic drugs, and to assess whether QTc lengthening was associated with certain psychotropic drugs and other risk factors. One hundred and sixty three patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(16 citation statements)
references
References 8 publications
1
13
0
2
Order By: Relevance
“…However, some studies reported no sex difference in QTc prolongation (Ozeki et al 2010). Other studies failed to detect female gender as a significant risk factor (Reilly et al 2000;Chong et al 2003;Rettenbacher et al 2005), or even QTc prolongation was found more commonly in male patients than in female patients (Ozeki et al 2010). Female gender is known to be a risk factor for QTc prolongation (Taylor 2003;Vieweg et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…However, some studies reported no sex difference in QTc prolongation (Ozeki et al 2010). Other studies failed to detect female gender as a significant risk factor (Reilly et al 2000;Chong et al 2003;Rettenbacher et al 2005), or even QTc prolongation was found more commonly in male patients than in female patients (Ozeki et al 2010). Female gender is known to be a risk factor for QTc prolongation (Taylor 2003;Vieweg et al 2009).…”
Section: Discussionmentioning
confidence: 93%
“…On multiple regression analysis, age and dose of the antipsychotic drug were predictors for QT prolongation. A further study in 163 psychiatric inpatients (36% female, age 24-86 years) on antipsychotic drugs, with no indication of how QTc was calculated, found a QTc > 453 ms in 7% (Chong et al, 2003). Significant predictors for QT prolongation in a logistic regression model were the use of chlorpromazine, flupenthixol decanoate and fluphenazine decanoate.…”
Section: Prevalence Of Qt Prolongation In Psychiatric Patientsmentioning
confidence: 97%
“…Flupenthixol, a phenothiazine derivate, was identified as significant predictor for QT prolongation in a study in 163 psychiatric inpatients with no indication of how QTc was calculated (36% female, age 24-86 years) (Chong et al, 2003). No occurrence of TdP has been reported in association with this drug.…”
Section: Flupenthixolmentioning
confidence: 98%
See 1 more Smart Citation
“…We included studies on cardiovascular comorbidity, which as a minimum criterion used a control group (9,59,(173)(174)(175)(176)(177)(178)(179)(180)(181)(182)(183)(184)(185)(186)(187)(188)(189)(190). Overall, these studies, some of which were population-based, showed that cardiovascular problems are more frequent among people with schizophrenia than in control populations, although in terms of specific disorders the overall picture was heterogeneous.…”
Section: Cardiovascular Disease (568 Medline Hits)mentioning
confidence: 99%